The nature of learning using research to inspire practice - Dumont, Hanna (OECD, 2010)
Literaturangaben
Franz. Ausg. u. d. T.: Comment apprend-on? La recherche au service de la pratique
Keywords: Lernen; Aufsatzsammlung